Dietary intake of branched-chain amino acids and colorectal cancer risk. Issue 1 (14th July 2021) - Rossi, Marta; Mascaretti, Federica; Parpinel, Maria; Serraino, Diego; Crispo, Anna; Celentano, Egidio; Giacosa, Attilio; La Vecchia, Carlo
Abstract: An adequate intake of branched-chain amino acids (BCAA) is required for protein synthesis and metabolic functions, including insulin metabolism. Emerging studies found positive associations between BCAA and the risk of various diseases sharing aetiological aspects with colorectal cancer (CRC), including type 2 diabetes, obesity and pancreatic cancer. We investigated the relation between dietary BCAA and CRC using data from a multicentric Italian case–control study, including 1953 cases of CRC (of these, 442 of sigmoid colon) and 4154 hospital controls with acute, non-neoplastic diseases. A validated FFQ was used to estimate the participants' usual diet and to assess dietary intakes of various nutrients, including energy, BCAA and Ca. OR and corresponding CI were computed by multiple logistic regression models adjusted for age, sex and other confounding factors, including total energy intake. BCAA intake was inversely related to CRC risk (OR for the highest v . the lowest quintile 0·73; 95 % CI 0·55, 0·97), but the association was attenuated after adjustment for Ca intake (OR 0·90; 95 % CI 0·65, 1·25). An inverse association with sigmoid colon cancer risk also remained after adjustment for other dietary factors, including Ca intake (OR 0·49; 95 % CI 0·27, 0·87). This study provides supporting evidence that higher levels of dietary BCAA intake are not associated with an increase of CRC risk, but confirms that they may be related to a reduced risk of sigmoid colon cancer.